2013
DOI: 10.1021/jp404829y
|View full text |Cite
|
Sign up to set email alerts
|

Free Energetics of Arginine Permeation into Model DMPC Lipid Bilayers: Coupling of Effective Counterion Concentration and Lateral Bilayer Dimensions

Abstract: Mechanisms and underlying thermodynamic determinants of translocation of charged cationic peptides such as cell-penetrating peptides across the cellular membrane continue to receive much attention. Two widely-held views include endocytotic and non-endocytotic (diffusive) processes of permeant transfer across the bilayer. Considering a purely diffusive process, we consider the free energetics of translocation of a mono-arginine peptide mimic across a model DMPC bilayer. We compute potentials of mean force for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 70 publications
3
83
1
Order By: Relevance
“…Permeations of arginine amino acids or side chains were illustrated computationally and experimentally. 8, 1112, 3234 On the other hand arginine experiments are not necessarily a measure of charge effect on permeation. For example, it is possible that the long hydrophobic chain of arginine facilitates its permeation and not necessarily the charge, which is the focus of our discussion here.…”
Section: Resultsmentioning
confidence: 99%
“…Permeations of arginine amino acids or side chains were illustrated computationally and experimentally. 8, 1112, 3234 On the other hand arginine experiments are not necessarily a measure of charge effect on permeation. For example, it is possible that the long hydrophobic chain of arginine facilitates its permeation and not necessarily the charge, which is the focus of our discussion here.…”
Section: Resultsmentioning
confidence: 99%
“…This is because our focus is on the interactions between lipid and proteins without the complications of salt–lipid and salt–protein interactions. As indicated in a recent review on force fields (Sun et al, 2015), there is ongoing debates and refinement of force field parameter for ion or salt interactions with lipids, particularly charged lipids (Pandit and Berkowitz, 2002; Bockmann et al, 2003; Pandit et al, 2003; Mukhopadhyay et al, 2004; Cordomi et al, 2009; Pastor and Mackerell, 2011; Hu et al, 2013; Venable et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…All atom force fields, like CHARMM and AMBER, united atom force fields, like CHARMM—united atom, GROMOS and mixed all atom and united atom force fields are constantly developed and parameterized with experiments. At present, all atom force fields have limitations in simulating membrane potential and ion-lipid interactions involving protein, and are therefore not ready to simulate large, multiple component membrane systems containing anionic lipids, ions and protein (Cordomi et al, 2009; Pastor and Mackerell, 2011; Hu et al, 2013; Venable et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 However, other studies have shown that the system size can have a large influence on the result of charged solute partitioning. 55 In all simulations we used 128 lipids, resulting in a ratio of 64 lipids per solute, which should be sufficient for the uncharged solutes studied in this work. By using two solutes two free energy profiles are obtained, and an averaged profile with error bars could be calculated.…”
Section: A Molecular Dynamics Simulationsmentioning
confidence: 99%